Design and Simulation of Tracked Fire Fighting Robot based on RecurDyn - Zhang Xiangliang; Zhang Hua; Xiong Gen; Zhou Yilin (Jixie chuandong)
To design a crawler fire-fighting robot for diverse working environments， the reliability and stability are even more important. By utilizing the crawler-type chassis structure and the damping spring shock absorber used as the damping system， the traditional vibration problems caused by the traditional crawler structure are overcome. The motion equation is derived by the kinematics analysis on the robot crawling ladder. By conducting the simulation analysis on the crawling process of the designed crawler fire-fighting robot under the Track LM module of RecurDyn， the driving torque required for the robot ladder is obtained. According to the curve of gravity change obtained by simulation tests， the stability analysis on the robot to crawl ladder is achieved.